Displacement behaviour regulates the experience of stress in men. (March 2013) - Mohiyeddini, Changiz; Semple, Stuart
<x xml:space="preserve">Abstract</x> Behavioural coping strategies represent a key means by which people regulate their stress levels. Attention has recently focused on the potential role in coping of 'displacement behaviour' – activities such as scratching, lip biting and face touching. Increased levels of displacement behaviour are associated with feelings of anxiety and stress; however, the extent to which displacement behaviour, as a short-term behavioural response to emotionally challenging stimuli, influences the subsequent experience of stress remains poorly understood. The aim of this study was to investigate the potential role of displacement behaviour in coping with stress. In a study population of 42 healthy adult men (mean age = 28.09 years, SD = 7.98), we quantified displacement behaviour during a Trier Social Stress Test (TSST), and used self-report questionnaires to assess trait and state anxiety before the TSST, and the experience of stress afterwards. We predicted displacement behaviour would diminish the negative impact of the stressful situation, and hence be associated with lower post-TSST stress levels. Furthermore, we predicted displacement behaviour would mediate the link between state and trait anxiety on the one hand and the experience of stress on the other. Results showed the rate of displacement behaviour was positively correlated with state anxiety but unrelated to trait anxiety, and negatively correlated with the self-reported experience of stress, in agreement with the idea that displacement behaviour has a crucial impact on regulation of stress. Moreover, serial mediation analyses using a bias-corrected bootstrapping approach indicated displacement behaviour mediated the relationship between state anxiety and the experience of stress, and that state anxiety and displacement behaviour – in combination, respectively – mediated the link between trait anxiety and experience of stress. These results shed important new light on the function of displacement behaviour, and highlight promising new avenues for research into emotional expression and stress regulation.